Budaya Patriarki Kepemimpinan Perempuan dalam Sistem Politik di Indonesia Perspektif Maqashid Syariah - Meilani Putri Basri; A. St. Aqilah Nur Asizah; Kurniati (Al-Qolamuna: Journal Komunikasi dan Penyiaran Islam, 2025)
This research employs a qualitative, descriptive-analytical method focused on in-depth explanations of phenomena through the examination of texts, concepts, and social realities. The approaches employed are normative-theological and sociological, combined within a library research framework. The normative-theological approach is evident through the analysis of secondary data in the form of authoritative Islamic sources, such as verses of the Quran, the Prophet's hadith, and interpretations by classical and contemporary scholars discussing the principles of justice, welfare, equality, and the position of women in Islam. The research also explores the thoughts of scholars and relevant religious literature to explore the theological foundations of women's leadership from the perspective of Maqasid Sharia. Furthermore, the use of a sociological approach provides space to understand how these religious values ​​interact with social and cultural realities that shape the construction of women's roles, particularly in the context of Indonesian political life, which is still strongly entrenched in patriarchal culture. This research also utilizes national legal regulations, such as the 1945 Constitution and Law Number 39 of 1999 concerning Human Rights, as a basis for assessing the extent to which the principles of equality and non-discrimination are accommodated in the Indonesian political and legal system. In addition to examining normative texts, this research enriches the analysis by examining relevant empirical data, including various previous studies, scientific articles, policy reports, and academic studies that have discussed women's involvement in political leadership. By combining normative and empirical dimensions, this research not only uncovers a theoretical framework regarding the position of women in Islam but also explores the social realities that influence the application of these values ​​in modern political life.  Abstrak Penelitian ini menggunakan metode kualitatif deskriptif-analitis yang berfokus pada penjelasan mendalam terhadap fenomena melalui penelaahan teks, konsep, dan realitas sosial. Pendekatan yang digunakan adalah normatif-teologis dan sosiologis, yang dikombinasikan dalam kerangka studi pustaka (library research). Pendekatan normatif-teologis tampak melalui analisis terhadap data sekunder berupa sumber-sumber keislaman otoritatif, seperti ayat-ayat Al-Qur’an, hadits Nabi, serta tafsir ulama klasik maupun kontemporer yang membahas prinsip-prinsip keadilan, kemaslahatan, kesetaraan, dan kedudukan perempuan dalam Islam. Penelitian juga menelusuri pemikiran ulama dan literatur keagamaan yang relevan untuk menggali landasan teologis mengenai kepemimpinan perempuan dalam perspektif Maqashid Syariah. Di sisi lain, penggunaan pendekatan sosiologis memberi ruang untuk memahami bagaimana nilai-nilai keagamaan tersebut berinteraksi dengan realitas sosial dan budaya yang membentuk konstruksi peran perempuan, khususnya dalam konteks kehidupan politik Indonesia yang masih kental dengan budaya patriarki. Penelitian ini juga memanfaatkan regulasi hukum nasional seperti Undang-Undang Dasar 1945 dan Undang-Undang Nomor 39 Tahun 1999 tentang Hak Asasi Manusia sebagai pijakan untuk menilai sejauh mana prinsip kesetaraan dan non-diskriminasi diakomodasi dalam sistem politik dan hukum di Indonesia. Selain menelaah teks-teks normatif, penelitian ini memperkaya analisis dengan mengkaji data empiris yang relevan, termasuk berbagai penelitian terdahulu, artikel ilmiah, laporan kebijakan, serta studi-studi akademik yang telah membahas keterlibatan perempuan dalam kepemimpinan politik. Dengan menggabungkan dimensi normatif dan empiris, penelitian ini tidak hanya mengungkap kerangka teoretis mengenai posisi perempuan dalam Islam, tetapi juga menelusuri realitas sosial yang mempengaruhi penerapan nilai-nilai tersebut dalam kehidupan politik modern.